1998
DOI: 10.2527/1998.7682138x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a direct-fed yeast culture on enteric microbial populations, fermentation acids, and performance of weanling pigs.

Abstract: In three replicate trials, a total of 36 pigs that had been cannulated at the terminal ileum were used to determine the effects of a Saccharomyces cerevisiae culture in a phase feeding program (phase I was d 0 to 7 and phase II was d 8 to 21) on performance, ileal microflora, and short-chain fatty acids in weanling pigs. Pigs were cannulated at approximately 12 d of age, weaned at 17 d of age, and randomly assigned to one of three treatments: 1) a pelleted phase feeding program, 2) a similar program with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
71
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 0 publications
18
71
2
2
Order By: Relevance
“…Kratzer (1983, 1984) showed that there were no significant differences in weight gains of chickens given diets with or without Lactobacillus cultures. On the contrary, Mathew et al (1998) claimed that weanling pigs fed a yeast culture had better growth performance. The contradictory results might be attributed to the variation of Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 92%
“…Kratzer (1983, 1984) showed that there were no significant differences in weight gains of chickens given diets with or without Lactobacillus cultures. On the contrary, Mathew et al (1998) claimed that weanling pigs fed a yeast culture had better growth performance. The contradictory results might be attributed to the variation of Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 92%
“…These actions can result in cellular death (26). Several studies have shown that effects on the reduction in Enterobacteriaceae, coliforms, and E. coli numbers were related to VFA concentrations, but correlations were not determined (6,13,15,16,28). In this study, a correlation with Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…: +48 81 445 67 46 ted on various animal species (mainly cattle and pigs) indicate that the use of this species of yeast has multifaceted benefits, due in part to its chemical composition and biochemical functions (Wójcik et al 2008,According to Davis et al (2004) and Wójcik et al (2008), an immune activation effect can be attributed to Saccharomyces cerevisiae, while according to Mourfo et al (2005) it has an inhibitory effect on the replication of pathogenic bacteria and their toxins. SC yeast also stimulate replication of the saprophytic microflora of the digestive tract, which has been demonstrated in studies by Mathew et al (1998) and Baurhoo et al (2009).…”
Section: Introductionmentioning
confidence: 99%